Lung function and chronic respiratory symptoms of pig farmers: focus on exposure to endotoxins and ammonia and use of disinfectants. Issue 10 (October 1995) - Preller, L; Heederik, D; Boleij, J S; Vogelzang, P F; Tielen, M J
Abstract : OBJECTIVES--The prevalence of chronic respiratory symptoms among pig farmers is known to be high, but the aetiology of these symptoms is not yet unravelled. Long term average exposure to dust was evaluated, endotoxins and ammonia and use of disinfectants were compared with chronic respiratory symptoms and depressed base line lung function. METHODS--A cross sectional study was performed among 194 Dutch pig farmers, of whom 100 had not and 94 had chronic respiratory symptoms. Exposure-response relations were evaluated with multiple logistic and linear regression analysis. Estimates of long term average exposure were based on two personal exposure measurements, taken on one day in summer and one day in winter. Information on use of disinfectants and disinfection procedures was assessed by a walk through survey and interview by telephone. RESULTS--Exposure to dust, endotoxins, and ammonia were not related to chronic respiratory symptoms. Duration of the disinfection procedure and pressure used at disinfection were strongly and positively related to chronic respiratory symptoms. A significant inverse association between base line lung function and endotoxin exposure was found only among asymptomatic farmers. Ammonia exposure and duration of the disinfection procedure were significantly associated with base line lung function in the entire population. CONCLUSION--Results suggest that use of disinfectants is an important aetiological factor in chronic respiratory health effects of pig farmers. This factor has not been studied before. Results also suggest an aetiological role for exposure to endotoxins and ammonia in development of chronic respiratory health effects, but longitudinal studies with detailed exposure assessment strategies are required to assess their roles.